Design of Maximum Power Point Tracking Photovoltaic System Based on Incremental Conductance Algorithm using Arduino Uno and Boost Converter - Efendi S Wirateruna; Mohammad Jasa Afroni; Fawaidul Badri (Unusa Press, 2021)
Fossil fuel reserves are limited while the growing demand for energy utilization. It leads to an acceleration of renewable energy use. One of the renewable energy resources is solar energy, called the photovoltaic system. This paper uses a photovoltaic solar system consisting of a solar panel module, DC-DC boost converter, voltage divider, ACS712 as a current sensor, Arduino Uno, and load resistor. Maximum Power Point Tracking (MPPT) controller is implemented to track the maximum power point of the solar panel system using a boost converter based on the Incremental Conductance algorithm embedded in Arduino UNO. The PV system with MPPT controller is designed with PV 20 W. The testing of the ACS712 current sensor and voltage sensor show error values of about 1.82% and 0.83%, respectively, which are acceptable limits. Besides, the DC-DC boost converter is also tested, and its performance shows an increase in the output voltage. The test result of the PV system with MPPT control based on the Incremental Conductance algorithm shows the average value of the PV power output with resistive load at 36 Ω is about 7.34 W, while the PV system without MPPT is about 6.07 W. Thus, the Photovoltaic system using MPPT controller based on the incremental conductance algorithm can control PV power output at the maximum power point.